Pengembangan Aplikasi SINIBID untuk Penilaian Praktik Kebidanan - Nur aini; Yulia Herawati; Daniah Rendi (HEALTH CARE : JURNAL KESEHATAN, 2021)
COVID-19 pandemic has had a wide impact on various sectors, especially education. Countries around the world are implementing policies to prevent transmission by limiting face-to-face meetings at schools and universities with e-learning. For health students, such as midwifery STIKes Mita RIA Husada, who apply practical learning, they need a breakthrough so that the evaluation of skills runs optimally. The purpose of this study is to develop a website-based application for learning the clinical practice of midwife students during the Covid-19 pandemic and to test the user experience. The method used in this study is the Analysis, Development, Implementation, Evaluation (ADIE) method. In the User Experience evaluation stage, online data collection uses the User Experience Questionnaire (UEQ) tools. The population and sample were 41 students of applied midwifery SMRHJ. The results of the SMRHJ analysis used a paper checklist in a practice assessment. During the development, the SINIBID application has been produced for website-based midwifery practice assessment with the link http://sinibid.id/. The results of the user experience test for several groups of UEQ testing categories, namely the attractiveness of the application above the average (1.23), in terms of application clarity below the average (0.77), in terms of efficiency above the average (1.19), application accuracy is below average (1.06), application stimulation is good (1.42), and novelty is also stated to be good (1.27). Conclusion: the SINIBID application is useful and good for use in the learning process of midwifery students. aspects of clarity that are still lacking to be addressed by adding instructions for use.